Advancing Human Rights through Legal Advocacy in Community Service Projects - Riskayani Djamaleng; Indah Permata Sari (Community Service Journal of Law, 2023)
The protection and promotion of human rights are critical challenges in today’s global society, with social injustices and systemic inequalities affecting numerous individuals and communities. Legal advocacy in community service projects has gained attention as a means to address human rights issues at the grassroots level. This research aims to explore the multifaceted aspects of advancing human rights through legal advocacy in community service projects, bridging the gap between theory and practice. A mixed-method research approach is adopted, combining qualitative and quantitative methods. A Literature Review provides theoretical foundations, while Case Studies analyze community service initiatives with a human rights focus. Focus Group Discussions and Surveys gather data from stakeholders to understand the impact of legal advocacy interventions. The research reveals the transformative potential of legal advocacy in advancing human rights. Case studies show improvements in human rights conditions, empowering vulnerable communities through legal information and representation. Focus Group Discussions highlight increased awareness and agency among participants, challenging discriminatory practices. Survey data corroborates the effectiveness of legal advocacy in addressing human rights issues and promoting systemic change.